Formulation‐based approaches for dermal delivery of vaccines and therapeutic nucleic acids: Recent advances and future perspectives - Marwa A. Sallam; Supriya Prakash; Ninad Kumbhojkar; Charles Wyatt Shields IV; Samir Mitragotri (Wiley, 2021)
Abstract A growing variety of biological macromolecules are in development for use as active ingredients in topical therapies and vaccines. Dermal delivery of biomacromolecules offers several advantages compared to other delivery methods, including improved targetability, reduced systemic toxicity, and decreased degradation of drugs. However, this route of delivery is hampered by the barrier function of the skin. Recently, a large body of research has been directed toward improving the delivery of macromolecules to the skin, ranging from nucleic acids (NAs) to antigens, using noninvasive means. In this review, we discuss the latest formulation‐based efforts to deliver antigens and NAs for vaccination and treatment of skin diseases. We provide a perspective of their advantages, limitations, and potential for clinical translation. The delivery platforms discussed in this review may provide formulation scientists and clinicians with a better vision of the alternatives for dermal delivery of biomacromolecules, which may facilitate the development of new patient‐friendly prophylactic and therapeutic medicines.